2016
DOI: 10.1063/1.4972559
|View full text |Cite
|
Sign up to set email alerts
|

Undoped p-type GaN1–xSbx alloys: Effects of annealing

Abstract: We report p-type behavior for undoped GaN 1-x Sb x alloys with x ! 0.06 grown by molecular beam epitaxy at low temperatures (400 C). Rapid thermal annealing of the GaN 1-x Sb x films at temperatures >400 C is shown to generate hole concentrations greater than 10 19 cm À3 , an order of magnitude higher than typical p-type GaN achieved by Mg doping. The p-type conductivity is attributed to a large upward shift of the valence band edge resulting from the band anticrossing interaction between localized Sb levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The n-to-p conversion by incorporating Sb is special. Limited data were reported for the group V anion instead of cation doping on GaN [18][19][20][21][22]. Our work can have its contribution on the HMA field for further development.…”
Section: Resultsmentioning
confidence: 92%
“…The n-to-p conversion by incorporating Sb is special. Limited data were reported for the group V anion instead of cation doping on GaN [18][19][20][21][22]. Our work can have its contribution on the HMA field for further development.…”
Section: Resultsmentioning
confidence: 92%
“…Processes of MBE growth with As [42][43][44][45] and Sb [46,47] as surfactants were performed to increase the quality of GaN films. Furthermore, as incorporation into GaN changes the electronic properties of the host [48][49][50][51], antimony was also used to modify the properties of GaN [52][53][54] and to form GaNSb films with a p-type character [55,56]. The interaction of As and Sb with GaN, as well as the morphological changes caused by postdeposition annealing, have been studied [57,58], where it was shown that thermal treatment leads to easy desorption of the films, but some adsorbated atoms remain on the surface, modifying its properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that alloying of GaN with GaSb can produce a p-type GaNSb. 43 This effect was explained by a rapid upward shift of the VBM upon introduction of Sb into GaN. Since as we have shown in the Sec.…”
Section: Electrical Properties Of Zno 1−x Te X Hmasmentioning
confidence: 80%
“…This is in contrast to GaNSb alloys where p-type conductivity was achieved when both VBM and CBM were separated by about 0.5 eV from E FS . 43…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%